Trends in grades: UP School of Economics - Gwendolyn R. Tecson (University of the Philippines, School of Economics (UPSE), 2011)
Grades are used to evaluate students as well as to compare their scholastic achievements. They are used by graduate schools as well as business firms to discriminate between students. But when grades are inflated, they cease to be an objective measure. We therefore wish to examine the trend in grades in the UP School of Economics. In particular, we would like to find out if the explosion in Latin honors (cum laudes and magna cum laudes) in recent years is due to the Revitalized General Education Program (RGEP). Through regression analysis, we found that GWA is determined by the RGEP (as well as the EWA). Except for a few subjects, there is no grade inflation in RGEP courses.
Keywords: 330; Studierende; Bildungsniveau; Test; Wirtschaftsstudium; Philippinen